2021
DOI: 10.1109/access.2021.3100076
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Forecasting for the Electricity Spot Prices With Extreme Values Treatment

Abstract: Nowadays, modeling and forecasting electricity spot prices are challenging due to their specific features, including multiple seasonalities, calendar effects, and extreme values (also known as jumps, spikes, or outliers). This study aims to provide a comprehensive analysis of electricity price forecasting by comparing several outlier filtering techniques followed by various modeling frameworks. To this end, extreme values are first treated with five different filtering techniques and are then replaced by four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Zhang et al [7] predicted wheat production forecast on a country level using ensemble learning. I. Shah et al [8,9,10,11,12] and N.Bibi et al [13] have suggested many methods to predict the electricity demands and prices for various times, i.e., short term, medium-term, and long-term as well. But, electricity demands may vary largely in restaurants or meal delivery centers as it, in turn, depends on the order of their meals/products.…”
Section: Literature Surveymentioning
confidence: 99%
“…Zhang et al [7] predicted wheat production forecast on a country level using ensemble learning. I. Shah et al [8,9,10,11,12] and N.Bibi et al [13] have suggested many methods to predict the electricity demands and prices for various times, i.e., short term, medium-term, and long-term as well. But, electricity demands may vary largely in restaurants or meal delivery centers as it, in turn, depends on the order of their meals/products.…”
Section: Literature Surveymentioning
confidence: 99%
“…One can see that there are some extreme values (outliers) present in the demand series, especially at midnight hours. In general, these extreme values are identified and replaced by many methods [53]. In this research work, they are treated by the moving filter on-demand method suggested by Borovkova and Permana [54].…”
Section: Moving Filter On Demandmentioning
confidence: 99%
“…One of the best examples of energy consumption can be a household where energy consumption takes place in the form of electricity, gas etc. [1,2] The building sector is the most critical factor affecting greenhouse gas emissions, contributing onethird of energy-related EU emissions. The combination of fossil fuel energy and the production of electricity and heat across the buildings are influencing Greenhouse gas emissions [3].…”
Section: Introductionmentioning
confidence: 99%